El genero cladocolea TIEGH. (LORANTHACEAE) en México - Galván González, Luis Gil (Universidad Autónoma Metropolitana, 2016)
Loranthaceae family contains about 77 genus, including the genus Cladocolea Tiegh. which groups about 30 species. In 1975, Kuijt made the taxonomic treatment of Cladocolea. Since then it has not been the integral study of the genus, although new species have been described and new combinations have been proposed. So the taxonomic treatment of genus Cladocolea for Mexico was made. Descriptions, iIlustrations, distribution maps and a key to species of Cladocolea were included. 19 species of Cladocolea were registered for Mexico, included a new species (Cladocolea spathiflora ined.). The names C. pedicellata Kuijt and C. biflora Kuijt were excluded, as they are considered taxonomic synonyms of C. diversifolia (Benth.) Kuijt and Schoepfia schreberi J.F. Gmel. Cladocolea species are distributed in 17 states of Mexico, Guerrero state contains the greatest diversity of species and the highest number of endemisms. The vegetation types that have the greatest species richness are the cloud forest, mixed Pinus-Quercus forest and the Quercus forest. According to Kuijt (1975), Cladocolea is distinguished by its simple and determinate inflorescenses and by its flowers whit a basal bract, whitout lateral bracts, however the presence of determinate inflorescences was not constant in all species, so there are doubts about its circumscription. Anatomical and developtmental studies of flowers and inflorescences are required to resolve evolutive relationships between Cladocolea species and othe genera of Loranthaceae family.; La familia Loranthaceae contiene aproximadamente 77 géneros, incluyendo al género Cladocolea Tiegh. que agrupa alrededor de 30 especies. En 1975, Kuijt realizó el tratamiento taxonómico del género Cladocolea. Desde entonces no se ha abordado el estudio integral del género, a pesar de que se han descrito nuevas especies y se han propuesto nuevas combinaciones. Por lo que se realizó el tratamiento taxonómico del género Cladocolea para México. Se incluyeron descripciones, ilustraciones, mapas de distribución y una clave de identificación. Se registraron 19 especies de Cladocolea para México, incluída una especie nueva (Cladocolea spathiflora ined.). Se excluyeron los nombres de C. pedicellata Kuijt y C. biflora Kuijt ya que se consideran sinónimos taxonómicos de C. diversifolia (Benth.) Kuijt y Schoepfia schreberi J.F. Gmel. Las especies de Cladocolea se distribuyen en 17 estados del país y Guerrero contiene la mayor diversidad de especies y el mayor número de endemismos. Los tipos de vegetación que albergan la mayor riqueza son los bosques mesófilos de montaña, los bosques mixtos de Pinus-Quercus y los bosques de Quercus. De acuerdo a Kuijt (1975) Cladocolea se distingue por sus inflorescencias simples, determinadas y por sus flores con una bráctea basal y sin brácteas laterales, sin embargo la presencia de inflorescencias determinadas no fue constante en todas las especies, por lo que existen dudas acerca de su circunscripción. Se requieren estudios anatómicos y del desarrollo de flores e inflorescencias, que permitan esclarecer las relaciones evolutivas entre las especies de Cladocolea y otros géneros de la familia Loranthaceae.